Experimental Candida albicans infection in conventional mice and germfree rats. - Rogers, T (1976)
Swiss-Webster white mice were intravenously infected with various doses of Candida albicans, and the viable units in their spleens, livers, lungs, and kidneys were determined at various intervals after challenge. The results showed that C. albicans multiplied to a greater extent in the kidneys of mice than in their spleens, lungs, or livers. The infection in mice was chronic; increasing numbers of C. albicans were observed in their kidneys until about 17 to 24 days postchallenge. Clearance of C. albicans from infected kidneys was not symmetrical, since the number of viable C. albicans in one kidney did not coincide with the viable counts observed in the opposite kidney of that same animal. Male and female mice did not differ in their overall susceptibility (50% lethal dose test) or in the number of viable C. albicans in the kidneys at various time intervals after infection. C. albicans also multiplied in the kidneys of germfree rats; however, the peak of the C. albicans infection in their kidneys occurred earlier than in those of conventional mice.